Що таке y-перехоплення p (x) = 2 (x ^ 2-4) (x-3)?

Що таке y-перехоплення p (x) = 2 (x ^ 2-4) (x-3)?
Anonim

Відповідь:

# x = -2,2,3 #

Пояснення:

Для y-перехоплення повинно бути

#p (x) = 0 #

це

# 2 (x ^ 2-4) (x-3) = 0 #

і ми отримуємо

# x ^ 2-4 = 0 # тому # x_1 = 2 # або # x_2 = -2 #

або

# x-3 = 0 # тому # x_3 = 3 #

і y-перехоплення #p (0) = 2 * (- 4) * (- 3) = 24 #

Мої виправлення.

Відповідь:

# "y-intercept" = 24 #

Пояснення:

# "встановити x = 0 для y-перехоплення" #

#p (0) = 2 (0-4) (0-3) = 2 (-4) (- 3) = 24 #